Axenfeld-Rieger Anomaly and Neuropsychiatric Problems—More than Meets the Eye - Saffari, Afshin; Ziegler, Andreas; Merkenschlager, Andreas; Krüger, Stefan; Kölker, Stefan; Hoffmann, Georg Friedrich; Syrbe, Steffen (Neuropediatrics, 2020)
Objective The main purpose of this article is to demonstrate the co-occurrence of Axenfeld-Rieger anomaly and neuropsychiatric problems as clinical signs of genetically determined cerebral small vessel disease in two patients.Case Study We report on two adolescent individuals with ocular anterior segment dysgenesis (Axenfeld-Rieger anomaly) presenting with neuropsychiatric symptoms. Both patients underwent cerebral magnetic resonance imaging showing white matter T2-hyperintensities involving different brain regions, suspective of cerebral small vessel disease. Genetic analysis revealed pathogenic mutations in the FOXC1 gene (patient 1) and the COL4A1 gene (patient 2), respectively.Conclusion We report on the co-occurrence of ocular anterior segment dysgenesis (Axenfeld-Rieger anomaly) and neuropsychiatric symptoms as clinical signs of genetically determined cerebral small vessel disease in two patients. In both patients, the cerebral lesions involved the frontotemporal regions, brain regions that control social behavior as well as executive and cognitive function, highlighting the fact that neuropsychiatric symptoms may be early clinical presentations of cerebral small vessel disease. We further provide a review of monogenic causes of pediatric cerebral small vessel disease, emphasizing the links to childhood-onset neuropsychiatric disease.
Keywords: Axenfeld-Rieger anomaly; ocular anterior segment dysgenesis; small vessel disease; FOXC1; COL4A1; neuropsychiatric symptoms